SOME FEATURES OF CELLULAR ENERGY SUPPLY OF THE BODY IN PREMATURE INFANTS WITH SEVERE FORMS OF PERINATAL PATHOLOGY - О. Годованець (Bukovynian State Medical University, 2024)
The nature of postnatal adaptation of newborns, their further growth, development, health status and quality of life largely depend on the well-being of intrauterine development and maturity at birth. Premature birth under hypoxia causes signifi cant metabolic disorders in the body, is accompanied by a high risk of severe organ dysfunction, which requires in-depth research to clarify the features of intracellular metabolism in order to further improve methods of diagnosis and treatment of newborns with various forms of perinatal pathology. Aim of the research. To study the trends of changes in energy metabolism in premature infants with severe forms of perinatal pathology to investigate the possibility of using them as additional criteria of hypoxic damage to the body in conditions of morphological and functional immaturity. Materials and methods. Clinical and laboratory examinations were performed on 68 newborns with severe forms of perinatal pathology at the gestational age of 32 to 34 weeks; the comparison group consisted of 27 conditionally healthy newborns at the gestational age of 34 to 37 weeks. Inclusion criteria for the main study group: gestational age at birth from 32 to 34 weeks, clinical signs of severe perinatal pathology. Exclusion criteria: gestational age at birth < 32 and ≥ 37 weeks, diagnosed congenital malformations and septic conditions. The list of diseases was determined according to the International Classifi cation of Diseases, X Revision. The following blood serum laboratory parameters were studied: lactate level, glycerol-3-phosphate dehydrogenase (GPDH) (EC 1.1.99.5), succinate dehydrogenase (SDH), NADH dehydrogenase (NADH) (EC 1.6.5.3); the electron transport chain coeffi cient (ETC) was calculated. Laboratory studies were performed using micromethods. The study was conducted in accordance with the provisions of GCP (1996), the Convention of the Council of Europe on Human Rights and Biomedicine (April 4, 1997), the Declaration of Helsinki of the World Medical Association (1964-2008), Order of the Ministry of Health of Ukraine No. 690 dated September 23, 2009 (as amended by Order of the Ministry of Health of Ukraine No. 523 dated July 12, 2012). Protocol of scientifi c research of the Biomedical Ethics Committee of BSMU dated September 12, 2015. Informed written consent was obtained from the parents of the patients before the study with an explanationof the purpose, objectives and methods of laboratory testing. Statistical processing of the results was performed using STATISTICA software (StatSoft Inc., USA, version 10). Comparison of quantitative indicators with normal distribution was performed using Student's t-test, and the probability of diff erences was considered statistically signifi cant at p<0.05. The complex of studies was conducted within the framework of the planned research topics of the Department of Pediatrics, Neonatology and Perinatal Medicine of the Bukovinian State Medical University: «Improvement of the areas of prognosis, diagnostics and treatment of perinatal pathology in newborns and infants, optimization of the schemes of catamenial observation and rehabilitation» (State registration No. 0115U002768, term of execution 01.2015-12.2019) and «Chronobiological and adaptive aspects and features of vegetative regulation in pathological conditions in children of diff erent age groups» (State registration No. 0122U002245, term of execution 01.2020-12.2024). Results. In newborns of the main group, in comparison with the control group, a signifi cant decrease in GFDH and SDH was found, which indicates a signifi cant impairment of the activity of enzymes of the respiratory chain and explains the lack of oxygen absorption in the body at the cellular and tissue level, causing the severity of the condition of newborns. Determination of the level of GPDH and SDH in the dynamics of observation in children showed some improvement in these indicators. In the severe condition of newborns, a signifi cant increase in the NADPH index was found, with a further probable increase in its level in the dynamics of observation. Calculations of ETC coeffi cient in cord blood showed a signifi cant decrease of this indicator in comparison with the control group. The identifi ed disorders of intracellular energy metabolism under hypoxia indicate the expediency of conducting comprehensive scientifi c research to study the possibilities of appropriate pharmacological correction to improve the eff ectiveness of treatment of severe forms of perinatal pathology in premature infants. Conclusions: 1. The results of the study revealed a signifi cant decrease in GPDH and SDH at elevated levels of NADPH and ETC coeffi cient, which confi rms the presence of signifi cant disturbances in intracellular energy metabolism and mitochondrial oxidation processes. 2. Timely detection of metabolic disorders with the determination of mitochondrial oxidation, in particular energy metabolism, is an important area for improving diagnostic measures in severe forms of perinatal pathology in preterm infants with hypoxic damage to the body in the pathogenesis.